The Effects of Tourism on the GDP of Macedonia, Montenegro and Serbia in the Process of European Integration - Slobodan Čerović; Miroslav Knežević; Danijel Pavlović (Amfiteatru Economic Journal, 2016)
Tourism is a socio-economic phenomenon exerting considerable economic, social and political impact, thus securing itself an important position in the overall economic growth. The principal purpose of this paper is to present the effects of the EU integration process on tourist movements in Serbia, Macedonia and Montenegro during the period 2006-2014, as 2006 was the year when one of the surveyed countries initiated EU accession negotiations, and tourism sector contribution to GDP in these countries in the period from 2002-2013 based on the data available for these years. To that end, the authors have compared the relationship between the number of foreign tourist arrivals and overnight stays and the GDP rates in the surveyed countries. Upon reviewing the available sources, the authors have reached the conclusion that during the EU integration period, an increase in the number of foreign tourists and overnight stays positively correlated with the GDP growth. EU integration process has had a positive bearing on tourism movements in the surveyed countries. The panel regression method has shown that despite a continuous increase in the number of foreign tourist arrivals, tourism sector still makes a modest direct contribution to the overall economic growth of the surveyed countries (Serbia, Montenegro, and Macedonia). Also, the Granger causality test was applied to demonstrate that it is not possible to predict GDP values in any of the surveyed countries based on the tourism revenue growth, while tourism contribution to GDP in Macedonia and Montenegro can be predicted based on their GDP.
Keywords: L83; C42; C12; N74; O52; 330; tourism; economic growth; GDP; EU integration; panel regression